(untitled) (Revista Direito em Debate, 2020)
This article aims to analyze the socioaffectivity in recomposed families to understand whether private autonomy is necessary for their recognition. Using the hypothetical-deductive method, three hypotheses have been established related to the constitution of recomposed families and the relationships between stepparents and their stepchildren in order to verify the need for manifesting the will of the parties for the recognition of socioaffective affiliation within this model of family. The methodology used was doctrinal, legislative and jurisprudence analysis. The most significant results achieved were the understanding of recomposed families in their most diverse forms of existence, as well as the socioaffectivity and its requirements, and finally, the choice of one of the hypotheses as the correct one to answer the problematic of the present study.